Analisis Petrofisika dan Evaluasi Zona Overpressure sebagai Perangkap Hidrokarbon di Cekungan Jawa Timur Utara - Michael Anggi; A. Haris; Rinaldo (Jurnal Penelitian Pendidikan IPA, 2025)
Errors in estimating pore pressure can cause blowouts during the drilling process, especially in overpressured zones. This study focuses on pore pressure estimation in the North East Java Basin using the approach, which is validated with field data. The well log data analyzed include resistivity, density, sonic velocity, and porosity, which are used to detect the presence of overpressure zones and identify reservoir potential. The results show that the overpressure zone begins at a depth of 4600 feet and lasts up to 9000 feet. The interval between 4800 to 7300 feet is identified as a potential reservoir, while seal rocks are found at 4000–4600 feet. The cross plot between sonic and density parameters shows the dominance of smectite minerals, indicating that perfect compaction has not occurred due to trapped fluids. This finding strengthens the suspicion that the overpressure formation mechanism is dominated by sediment loading. Precise pore pressure estimation is needed to reduce operational risks and optimize hydrocarbon exploration in this area.